Systematic Theoretical Study on Structural, Stability, Electronic, and Spectral Properties of Si2MgnQ (Q = 0, ±1; n = 1–11) Clusters of Silicon-Magnesium Sensor Material - Zhu, Ben-Chao; Deng, Ping-Ji; Zeng, Lu (Frontiers in Chemistry, 2019)
By using CALYPSO searching method and Density Functional Theory (DFT) method at the B3LYP / 6-311G (d) level of cluster method, a systematic study of the structures, stabilities, electronic and spectral properties of Si2MgQ n (n = 1-11; Q=0, ±1) clusters of silicon-magnesium sensor material, is performed. According to the calculations, it was found that when n > 4, most stable isomers in Si2MgQ n (n = 1-11; Q=0, ±1) clusters of silicon-magnesium sensor material are three-dimensional structures. Interestingly, although large size Si2MgQ n clusters show cage-like structures, silicon atoms are not in the center of the cage, but tend to the edge. The Si2Mg-1 1,5,6,8 and Si2Mg+1 3,4,7,9,10 clusters obviously differ to their corresponding neutral structures, which are in good agreement with the calculated values of VIP, AIP, VEA, and AEA. The relative stabilities of neutral and charged Si2MgQ n (n = 1-11; Q=0, ±1) clusters of silicon-magnesium sensor material is analyzed by calculating the average binding energy, fragmentation energy, second-order energy difference and HOMO-LUMO gaps. The results reveal that the Si2Mg0 3, Si2Mg-1 3, Si2Mg+1 3 clusters have stronger stabilities than others. NCP and NEC analysis results show that the charges in Si2MgQ n (n = 1-11; Q=0, ±1) clusters of silicon-magnesium sensor material transfer from Mg atoms to Si atoms except for Si2Mg+1 1, and strong sp hybridizations are presented in Si atoms of Si2MgQ n clusters. Finally, the infrared (IR) and Raman spectra of all ground state of Si2MgQ n (n = 1-11; Q=0, ±1) clusters of silicon magnesium sensor material are also discussed.